2019
DOI: 10.1039/c9sc01405e
|View full text |Cite
|
Sign up to set email alerts
|

De novo synthesis, structural assignment and biological evaluation of pseudopaline, a metallophore produced by Pseudomonas aeruginosa

Abstract: The first total synthesis and isolation of pseudopaline was reported, which allows determination and confirmation of the absolute configuration of the natural product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 46 publications
0
27
0
3
Order By: Relevance
“…By the time this article was prepared, Zhang et al published the asymmetric synthesis of 4a and 4b , along with the attribution of the ( S,S,S ) configuration (the one of 4b ) to the natural product. This synthesis relies, as the one the same authors proposed for compound 3 , on the conversion of the amino groups in sulfonamides which are engaged, in turn, in an asymmetric Tsuji–Trost and a Fukuyama–Mitsunobu reactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By the time this article was prepared, Zhang et al published the asymmetric synthesis of 4a and 4b , along with the attribution of the ( S,S,S ) configuration (the one of 4b ) to the natural product. This synthesis relies, as the one the same authors proposed for compound 3 , on the conversion of the amino groups in sulfonamides which are engaged, in turn, in an asymmetric Tsuji–Trost and a Fukuyama–Mitsunobu reactions.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, we present a new synthesis of the two epimers of pseudopaline ( 4 ). This approach represents an alternative strategy for the synthesis of pseudopaline (and, in general, of opine metallophores) to the one exploited by Zhang et al, thanks to a reduced number of steps (5, starting from commercially available 7 , vs. 8), comparable overall yields (24 % vs. 22 %), and greener conditions avoiding the use of transition metals, toxic oxidizing reagents, and of non‐atom efficient reactions (i.e. Fukuyama–Mitsunobu).…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that SaODH and PaODH would catalyze reversible reactions and that both enzymes would exclusively form the (R)-product diastereomer, consistent with structurally homologous opine dehydrogenases (18 -20). To test this hypothesis, (R)-and (S)-pseudopaline and (R)-and (S)-staphylopine were synthesized as previously described (10,21). SaODH or PaODH were combined with NADP ϩ and then mixed with varied concentrations of (R)-or (S)-staphylopine (SaODH) or (R)-or (S)-pseudopaline (PaODH) ( Fig.…”
Section: Saodh and Paodh Catalyze Reversible Reactionsmentioning
confidence: 99%
“…Interestingly, it was recently shown that when 100 M (S)pseudopaline is added to WT P. aeruginosa PAO1 grown on Vogel-Bonner minimal media with 50 M of added EDTA the intracellular concentrations of Zn(II), Fe(II), Co(II), and Ni(II) are increased (10). 100 M (R)-pseudopaline did not increase metal uptake compared with WT P. aeruginosa PAO1 grown in the absence of any added metallophore.…”
Section: Opine Dehydrogenase Stereospecificity and Mechanismmentioning
confidence: 99%
See 1 more Smart Citation